STRATEGIC PLANNING IN THE TURKISH PUBLIC SECTOR - (:unkn) unknown (BABES-BOLYAI UNIV, 2015)
New public management reforms require economic and democratic development together. The main concern could be considered how to increase the development of democratic representation and corporate management capacity of the local government. In this regard the re-distribution of public power (legal, financial, administrative and partially political) has been targeted to clarify responsibilities and identify new actors (legislation and practices). In this respect, it is important to examine all necessary legislation and implementation in order to analyze the experience of each country. This paper examined the Turkish public sector strategic planning experiences by focusing on the legal framework and some practices. A comprehensive survey conducted on some central public administration bodies was also used to reflect opinions and concerns from the practice of implementation as a valuable secondary source for this study.
Keywords: strategic planning; New Public Management; Turkish public sector reform